Comparative analysis of pathogenicity profiles and antitumour effects of wild and mutant strains of Salmonella enterica serovar Agona - Gwee, Chin Piaw (2015)
The fight against cancer has been a never ending battle. Cancer remains a major threat to human life. Limitations of conventional therapies included lack of selectivity, poor penetration and highly toxic to the host. One of the innovative approaches which have gained the interest of scientists from past few decades is the use of live, genetically modified bacteria as tumour therapy agent. Engineered bacteria possess unique features to overcome the limitations of conventional therapies. Low virulence and highly tolerability of Salmonella spp. in animals and humans make it as a most studied pathogen in regards to antitumour therapy. Genetically modified S. Typhimurium has been constructed as direct tumouricidal agent or as drug delivery vector in many researches. Main objective of this study is to construct genetically modified S. Agona as antitumour agent. A powerful genetic manipulation tool is needed in order to meet the requirements as tumouricidal agent in experimental and clinical research. Group II intron mutagenesis technology was exploited in current study to inactivate the metabolic genes in S. Agona. Group II intron technology has been shown to be able to insert at desired DNA at high frequency and specificity. In this study, LeuB and ArgD metabolic genes in S. Agona were successfully knockout at frequency of 15% and 3% respectively. Non-reverting and high stability of intron insertion was proven with a stability passage assay of 30 days culture. The constructed knockout S. Agona has become auxotrophic for leucine and arginine. Inactivation of LeuB and ArgD genes leads to a significant growth defect in M9 minimal media. Salmonella is a natural pathogen of mice, thus, mouse model was used to evaluate the potential pathogenicity and antitumour activity of engineered S. Agona in present work. Quadruple knockout BDLA exhibited highest safety among all of the strains in all tested parameters including bacterial colony forming units, immunity profile and histopathology studies. Tumour growth inhibition study was divided into two groups, which are small tumour model with size approximately 250 mm3 and large tumour model with size approximately 450 mm3 in comparison with each other.Results have shown that all of the stains are able to delay the growth of the small and large solid tumour as compare to the negative control, with better efficacy shown by auxotrophic knockout strain LA and BDLA. Interestingly, tumour growth inhibition noticed on small tumour is not as effective as seen on large tumour, might be due to the better hypoxia or nutrient conditions available in microenvironment of big tumour. Furthermore, findings from this study showed that the treated groups with repeated treatment did not show any significant improvement in tumour growth delay, in both big and small solid tumour models. Overall, the virulence of BDLA knockout strain was reduced and antitumour effect was successfully enhanced. The results obtained from current work suggest a great potential of auxotrophic quadruple knockout S. Agona as antitumour agent.